2018
DOI: 10.3390/f9070404
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Cyclonic Wind Storms Shapes Tropical Forest Dynamism and Functional Trait Dispersion

Abstract: As cyclonic wind storms (hurricanes and typhoons) increase in frequency and intensity with climate change, it is important to understand their effects on the populations and communities of tropical trees they impact. Using tree demographic data from four large, tropical forest dynamics plots that differ in cyclonic storm frequency, we compare tree population and community dynamics. Additionally, we assess the effect of cyclonic storms on three functional traits, specific leaf area, wood density, and tree heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 74 publications
1
63
0
Order By: Relevance
“…The community synchrony in the abundance of flowers and fruits counts at 4-6-year timescales is consistent with recurring ENSO positive anomalies (Fig.1). Therefore, the signal of ENSO on community synchrony in the reproductive effort of tropical trees in Luquillo exists despite a dynamic tree community situated in an aseasonal, disturbance-affected forest (Hogan et al 2016; Hogan et al 2018; Zimmerman et al 2007). A positive ENSO has no effect on rainfall at Luquillo but decreases temperature (strongest relationship at 2 to 4-month lead, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The community synchrony in the abundance of flowers and fruits counts at 4-6-year timescales is consistent with recurring ENSO positive anomalies (Fig.1). Therefore, the signal of ENSO on community synchrony in the reproductive effort of tropical trees in Luquillo exists despite a dynamic tree community situated in an aseasonal, disturbance-affected forest (Hogan et al 2016; Hogan et al 2018; Zimmerman et al 2007). A positive ENSO has no effect on rainfall at Luquillo but decreases temperature (strongest relationship at 2 to 4-month lead, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Such low mortality under typhoon disturbances has also been observed in other insular forests such as in the Philippines, southern Japan, and Jamaica, although not in Puerto Rico, the Solomon Islands, American Samoa, and an inland forest in southern China (Appendix ). Hogan et al (2018) showed that forests experiencing higher typhoon frequencies (including Fushan) are more resistant to typhoons as manifested by their low mortality and stable functional composition. Indeed, the majority of those low‐mortality forests (excluding the Jamaican one) are situated in the most typhoon‐prone region in the world, the northwest Asia–Pacific (Lin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A future research priority is to determine specific environmental variables that drive fluctuations of tree species abundances in specific forests. Over the time period studied, the forest plots we examined were buffeted by a range of environmental factors, such as drought (Condit et al 1996), groundfires (Baker et al 2008), hurricanes/typhoons (Yap et al 2016;Hogan et al 2018) and insect herbivory (Gonzalez-Akre et al 2016). Although many such factors can be identified, they are often idiosyncratic in nature and often act on population abundances via nonlinear causal pathways.…”
Section: Discussionmentioning
confidence: 99%